Nitrogen mineralization from organic materials and fertilizers: Predicting N release. Issue 2 (13th March 2020) - Cassity‐Duffey, Kate; Cabrera, Miguel; Gaskin, Julia; Franklin, Dory; Kissel, David; Saha, Uttam
Abstract: Organic growers use a wide range of organic fertilizers and materials to supply nutrients and meet plant demand of N. These products range from commercially processed animal and plant byproducts to composts and poultry litters. To better synchronize N release with plant demand, we investigated the rate and pool of potentially mineralizable N from 22 commercial, organic fertilizers; 15 poultry litters; and 11 composts. Fertilizers and organic materials were mixed with soil and inorganic N was measured over 99 days under optimal conditions (50% estimated water holding capacity and 30°C). Net N mineralized from the organic fertilizer or material was determined and fit to first‐order kinetics to determine the rate of mineralization ( k ) and the pool of mineralizable nitrogen (N0). Net N mineralized ranged from 25–93%, 10–55%, and 1–5% of the organic N applied for the fertilizers, poultry litters, and composts that mineralized, respectively. The pool of mineralizable N was accurately predicted from the initial total N of the materials, but no characteristics predicted the rate constant, k . Using a grouped approach based on product type and the percentage of N mineralized to determine k, we were able to predict net mineralized for fertilizers ( R 2 = 0.84) and poultry litters ( R 2 = 0.62).